Inhibition of PIM1 kinase attenuates bleomycin-induced pulmonary fibrosis in mice by modulating the ZEB1/E-cadherin pathway in alveolar epithelial cells. (September 2020) - Zhang, Xinyi; Zou, Yun; Liu, Yuqi; Cao, Yumeng; Zhu, Jiali; Zhang, Jianhai; Chen, Xia; Zhang, Rui; Li, Jinbao
Highlights: PIM1 was upregulated during the development of BLM induced lung fibrosis. PIM1 inhibitor SMI-4a ameliorated BLM induced pulmonary fibrosis by reversing alveolar epithelial to mesenchymal transition. PIM1 modulated EMT through modulating E-cadherin expression of alveolar epithelial cells. Alveolar epithelial PIM1 silencing by AAV9-shPIM1 injection intratracheally alleviates BLM induced pulmonary fibrosis. Abstract: PIM1 is serine/threonine protein kinase that is involved in numerous biological processes. Pulmonary fibrosis (PF) is a chronic pathological result of the dysfunctional repair of lung injury without effective therapeutic treatments. In the current study, we investigated whether PIM1 inhibition would improve bleomycin (BLM)-induced pulmonary fibrosis. In a BLM-induced pulmonary fibrosis model, PIM1 was persistently upregulated in fibrotic lung tissues. Furthermore, PIM1 inhibition by the PIM1-specific inhibitor SMI-4a showed protective effects against BLM-induced mortality. Furthermore, SMI-4a suppressed hydroxyproline deposition and reversed epithelial-mesenchymal transition (EMT) formation, which was characterized by E-cadherin and α-SMA expression in vivo. More importantly, the ZEB1/E-cadherin pathway was found to be closely associated with BLM-induced pulmonary fibrosis. After the in vitro treatment of A549 cells, PIM1 regulated E-cadherin expression by dependently modulating the activity of the transcription factor ZEB1. These findings were verified in vivo after SMI-4a administration. Finally, an shPIM1-expressing adeno-associated virus was delivered via intratracheal injection to induce a long-term PIM1 deficiency in the alveolar epithelium. AAV-mediated PIM1 knockdown in the lung tissues alleviated BLM-induced pulmonary fibrosis, as indicated by collagen accumulation reduction, pulmonary histopathological mitigation and EMT reversion. These findings enhance our understanding of the roles of PIM1 in BLM-induced pulmonary fibrosis and suggest PIM1 inhibition as a potential therapeutic strategy in chronic pulmonary injuries.